The role of EU agri-environmental measures preserving extensive grazing in two less-favoured areas in Portugal. (July 2016) - Jones, Nádia; Duarte, Filomena; Rodrigo, Isabel; van Doorn, Anne; de Graaff, Jan
Highlights: We analysed the effects of two agri-environmental measures in two areas in Portugal. These measures are aimed at preserving permanent pasture and extensive livestock. Stocking rate and soil cover (NDVI) were used as indicators of the policy performance. Participants complied with obligations and slightly increased livestock numbers. Soil cover was preserved by a reduction of grazing and an increase of stall feeding Abstract: Since 1992 agri-environmental issues have gained attention by reforms of the CAP. For instance by supporting environmentally friendly land use, such as permanent pastures in less-favoured areas (LFA) that are only marginally suitable for alternative farming practices. In the last two decades a significant part of agricultural land in Portugal has been converted to permanent pastures. The question is what role the EU agri-environmental measures (AEM) have played in that development. This paper assesses to which extent AEM have been effective in preserving and promoting permanent pastures and extensive animal production. We investigated two AEM in two research areas: Traditional Mixed Farming (TMF) in Centro and Extensive Grassland (EG) in Alentejo for the implementation period 2005–2009. Spatial information was analysed to link plot and farm characteristics with performance (result and impact) indicators such as stocking rate and soil cover (assessed through the normalised difference vegetation index (NDVI)). These indicators have been recognized as valuable indicators of AEM effects, and are therefore used in this research. A comparison was made between farms with certain AEMs and farms without these AEMs, that would be eligible for these specific AEMs. The results indicate that the participation in TMF and EG in preserving permanent pastures has been rather low in both regions. Nevertheless, these measures contributed to the upkeep of extensive livestock production with about 65% of participant farms achieving the expected policy result (maintenance or intensification of livestock keeping), although the effect was only significant in Centro. TMF and EG measures were effective in preserving the number of grazing livestock (goats and sheep, in Centro and Alentejo, respectively). These effects on livestock appeared to be associated with increased vegetation cover on participant farms in Centro, and with a tendency towards maintaining the pre-existing vegetation cover in Alentejo. Our results suggest that although AEM were effective in preserving grazing livestock, changes in grazing practices have not led to a significant improvement of the conditions to reduce the risk of wildfire and soil erosion. This should be taken into account in the design of new AEMs.